HUBUNGAN KONFLIK PERAN GANDA, KECERDASAN EMOSIONAL, DAN BEBAN KERJA TERHADAP KINERJA PERAWAT PASIEN LANSIA - Endarwati, Waode Khofifah; Susanty, Sri; Kusnan , Adius (Jurnal Ilmiah Keperawatan IMELDA, 2024)
Background: The performance of nurses tasked with caring for the elderly is greatly influenced by the quality of the services provided. Nurse performance is influenced by several factors, namely: ability, motivation, support received, job existence and nurses' organizational relationships in carrying out their duties to provide health services to patients. Method: This study employed a cross-sectional descriptive correlation design, with random sampling technique. Surveys were administered to assess the performance of nurses. The surveys included questions about the nurses' personal information, professional experience, and other factors that may affect their performance. The study was carried out at multiple healthcare facilities, specifically hospitals and health centers, with a sample size of 128 individuals. The employed analytical methods are Chi Square and multiple logistic regression. Results: There is a significant correlation between emotional intelligence and nurse performance (p=0.009), as well as between workload and nurse performance (p=0.026). Emotional intelligence is the most influential factor on nurse performance, with a statistically significant impact (p=0.027). Nevertheless, the presence of dual role conflict is not deemed to have a substantial correlation with the performance of nurses in delivering nursing services to senior patients. Conclusion: There exists a notable association between emotional intelligence and nurse performance (p=0.009), as well as between workload and nurse performance (p=0.026). Emotional intelligence has the greatest influence on nurse performance, with a statistically significant impact (p=0.027). However, the existence of dual role conflict is not considered to have a significant association with the performance of nurses in providing nursing services to elderly patients.